Deep Learning: Adaptive Solutions Towards Inclusive 21st Century Education - Randi Nur Ikhsan; Agus Setiawan (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
The demands of 21st-century education require a paradigm shift in learning that goes beyond the mere transfer of knowledge toward the development of critical thinking, creativity, collaboration, and communication skills. At the same time, the education system is expected to embody the principle of inclusivity to ensure that every learner has equal access to meaningful learning opportunities. This article aims to analyze the relevance and potential of deep learning pedagogy as an adaptive approach to support inclusive education in the 21st century. The study employed a library research method by reviewing academic literature, including books, reputable journal articles, and both national and international policy documents. The findings indicate that deep learning pedagogy emphasizes conceptual understanding, higher-order thinking, and active student participation, aligning with the demands of 21st-century competencies. Moreover, integrating deep learning with inclusivity principles allows diverse learners, including those with special needs, to engage actively through project-based, collaborative, and digital learning strategies. Nevertheless, the implementation in Indonesia faces several challenges, such as teachers’ readiness, limited facilities, and the dominance of teacher-centered practices. The article concludes that deep learning pedagogy offers a transformative solution for enhancing both quality and equity in education, while further empirical research is required to test its implementation in various educational contexts.